Pemberdayaan Ibu Rumah Tangga Melalui Pemanfaatan Minyak Jelantah Menjadi Lilin Aromaterapi - Putri Maysyarah; Dinda Maharani Siadari; Rosintan Sipayung; Yusmalinda; Jesika Melina Simamora (Yayasan Cerdas Pedia Indonesia, 2025)
This community service program addresses the environmental and health hazards of waste cooking oil (WCO) in Pematangsiantar, Indonesia. Improper disposal and repeated consumption of WCO cause significant ecological degradation and chronic diseases, including cancer and cardiovascular issues. Utilizing Participatory Action Research, this initiative empowered housewives in Perumahan Bersatu Maju through technical training in upcycling WCO into high-value aromatherapy candles. The process involved purification with activated charcoal and formulation using stearin to ensure quality and durability. Results indicated a significant improvement in participants' environmental literacy and technical proficiency. Economic analysis revealed a potential profit margin of approximately 97%, with production costs significantly lower than market prices. By transforming hazardous waste into creative economic assets, this program fosters family financial resilience and sustainable consumption practices. Ultimately, this initiative successfully shifts the paradigm from a linear economy toward circular management objectives.